Safety, pharmacokinetics, and pharmacodynamics of nomlabofusp (CTI‐1601) in Friedreich's ataxia - Russell Clayton; Teresa Galas; Noreen Scherer; Jennifer Farmer; Nancy Ruiz; Mohamed Hamdani; Devin Schecter; David Bettoun (Annals of Clinical and Translational Neurology, 2024)
Abstract Objective Current treatments for Friedreich's ataxia, a neurodegenerative disorder characterized by decreased intramitochondrial frataxin, do not address low frataxin concentrations. Nomlabofusp (previously CTI‐1601) is a frataxin replacement therapy with a unique mechanism of action that directly addresses this underlying frataxin deficiency. Phase 1 studies assessed the safety, pharmacokinetic, and pharmacodynamic profiles of subcutaneously administered nomlabofusp in adults with Friedreich's ataxia. Methods Patients were enrolled in two Phase 1, double‐blind, placebo‐controlled studies. The single ascending‐dose (SAD) study (NCT04176991) evaluated single doses of nomlabofusp (25, 50, 75, or 100 mg) or placebo. The multiple ascending‐dose (MAD) study (NCT04519567) evaluated nomlabofusp (25 mg daily for 4 days then every third day, 50 mg daily for 7 days then every 2 days, or 100 mg daily) or placebo for 13 days. Results Patients aged 19–69 years were enrolled (SAD, N = 28; MAD, N = 27). Nomlabofusp was generally well tolerated through 13 days. Most adverse events were mild and resolved quickly. No serious adverse events or deaths were reported. Peak nomlabofusp plasma concentrations occurred 15 min after subcutaneous administration. Nomlabofusp plasma exposures increased with increasing doses and daily administration and decreased with reduced dosing frequency. Increased frataxin concentrations were observed in buccal cells, skin, and platelets with higher and more frequent nomlabofusp administration. Interpretation Results from this study support a favorable safety profile for nomlabofusp. Subcutaneous nomlabofusp injections were quickly absorbed; higher doses and daily administration resulted in increased tissue frataxin concentrations. Future studies will evaluate longer‐term safety and possible efficacy of nomlabofusp.